1999
DOI: 10.1016/s0014-5793(99)00780-2
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the H19 gene and its function in human bladder carcinoma cell lines

Abstract: The human H19 gene is a paternally imprinted oncofetal gene, highly expressed in several fetal tissues, downregulated in nearly all adult tissues but re-expressed in carcinomas of tissues which express the gene in fetal life. It has no known protein product and till today, no function could be designated to H19 RNA. Cells derived from bladder carcinomas and hepatocellular carcinomas were transfected with plasmids carrying a luciferase reporter gene under the control of a 800 nucleotides long promoter region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The H19-Luc plasmid which contains the luciferase gene under the control of the human H19 promoter region from nucleotide -818 to + 14 was prepared as described [28]. The H19-Luc plasmid was digested with XbaI and NcoI, and the insert of the luciferase gene (luc) was replaced by the Diphtheria toxin A chain (DTA) coding region to yield the H19-DTA construct.…”
Section: Methodsmentioning
confidence: 99%
“…The H19-Luc plasmid which contains the luciferase gene under the control of the human H19 promoter region from nucleotide -818 to + 14 was prepared as described [28]. The H19-Luc plasmid was digested with XbaI and NcoI, and the insert of the luciferase gene (luc) was replaced by the Diphtheria toxin A chain (DTA) coding region to yield the H19-DTA construct.…”
Section: Methodsmentioning
confidence: 99%
“…All the luciferase gene reporter constructs were built from the pGL3 basic (Luc‐1) vector (Promega), which lacks both promoter and enhancer sequences. The construct Luc‐PBH19, which contains the reporter gene under the control of the human H19 promoter region from nucleotides −818 to +14, was prepared as described 6…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that transcription of the human H19 gene is under the control of regulatory sequences downstream to the coding sequence 6. We demonstrated that luciferase activity could be selectively expressed in cells transfected with a plasmid carrying the luc gene linked to the 814 bp 5′‐flanking region of the H19 gene 6. Our results showed that elements responsible for basal promoter activity are contained within the 85 bp upstream region and that cell specificity is mainly conferred by the 814 bp upstream sequences 7…”
mentioning
confidence: 99%
“…The lncRNA H19 is located on chromosome 11p15.5 and is 2.3 kb in length [ 13 ]. The H19 gene, which is a paternally imprinted onco-fetal gene, is typically down-regulated in adult tissues, but can be expressed in cancer tissues at levels similar to those observed in fetal life [ 14 ]. Many studies have confirmed that H19 is re-expressed in many types of solid tumors, such as breast cancer, gastric cancer, and esophageal cancer, and H19 expression is closely related to tumor invasion, metastasis, recurrence and poor prognosis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%